A new genus of cricket (Orthoptera: Gryllidae; Gryllinae) from East Asia - Storozhenko, Sergey Yu; Paik, Jong Cheol (Zootaxa, 2009)
The small cricket, Gryllus nipponensis, was described from Japan (Shiraki, 1913), but its generic position  was uncertain. It was placed in Gryllulus Uvarov, 1935 (Shiraki et al., 1950), and then Modicogryllus Chopard, 1961 (Chopard, 1961). Japanese authors included Gryllus nipponensis in the genus Comidogryllus Otte & Alexander, 1983 based on the shape of head and the acoustic pattern of the species (Ichikawa et al., 2000; Ichikawa et al., 2006). Later it was shown that Gryllus nipponensis was not congeneric with Australian species of Comidogryllus and placed it in Modicogryllus with uncertain subgeneric position (Storozhenko & Paik, 2007).